Polymer Interface-Dependent Morphological Transition toward Two-Dimensional Porous Inorganic Nanocoins as an Ultrathin Multifunctional Layer for Stable Lithium-Sulfur Batteries - Kim, Seongseop; Lim, Won Gwang; Im, Hyeonae; Ban, Minkyeong; Han, Jeong Woo; Lee, Jisung; Hwang, Jongkook; Lee, Jinwoo (Journal of the American Chemical Society, 2021)
Two-dimensional (2D) porous inorganic nanomaterials have intriguing properties as a result of dimensional features and high porosity, but controlled production of circular 2D shapes is still challenging. Here, we designed a simple approach to produce 2D porous inorganic nanocoins (NCs) by integrating block copolymer (BCP) self-assembly and orientation control of microdomains at polymer-polymer interfaces. Multicomponent blends containing BCP and homopoly(methyl methacrylate) (hPMMA) are designed to undergo macrophase separation followed by microphase separation. The balanced interfacial compatibility of BCP allows perpendicularly oriented lamellar-assembly at the interfaces between BCP-rich phase and hPMMA matrix. Disassembly of lamellar structures and calcination yield ultrathin 2D inorganic NCs that are perforated by micropores. This approach enables control of the thickness, size, and chemical composition of the NCs. 2D porous and acidic aluminosilicate NC (AS-NC) is used to fabricate an ultrathin and lightweight functional separator for lithium-sulfur batteries. The AS-NC layer acts as an ionic sieve to selectively block lithium polysulfides. Abundant acid sites chemically capture polysulfides, and micropores physically exclude them, so sulfur utilization and cycle stability are increased.
Keywords: Chemical compositions; Inorganic nanomaterials; Interfacial compatibility; Macro phase separation; Morphological transitions; Multicomponent blends; Polymer-polymer interfaces; Two Dimensional (2 D)